Enhancing the knowledge of parents on child health using eLearning in a government school in the semi-rural community of Karachi, Pakistan. - Saleema Gulzar; Sana Saeed; Salimah Taufiq Kirmani; Rozina Karmaliani (Public Library of Science (PLoS), 2022)
Education is one of the vital social determinants of health. Health and education share a symbiotic relationship for all cadre including children and adolescents to ensure that they are well equipped to combat the health risk in the environment. The current literature globally found some initiatives to create health awareness among school children. However, there is a dearth of studies available addressing parental health awareness through school platforms. Therefore, the current study aims to fill this gap, and the Aga Khan University School of Nursing and Midwifery initiated the School Health Program (SHP) in one of the remote communities in Sindh, Pakistan. The overall goal of the study was to improve children's health by enhancing the health awareness of the parents through school platforms utilizing online modalities. Another objective of this study was to identify the effect of using eLearning on parental knowledge and perceptions. The study utilized a sequential explanatory mixed-method design. Twelve health awareness sessions relevant to children's health using eLearning were conducted over one year. Parents' knowledge was assessed through a pre-posttest, which was administered after each teaching session. Subsequently, focused group discussions were carried out with parents, community leaders, and schoolteachers to gain insights regarding the effectiveness of the health education program. The pre-and post-test results showed again in knowledge in nine out of twelve sessions. The findings from qualitative content analysis yielded three key themes: Perceived usefulness of eLearning, Barriers affecting usability, and Way forward for eLearning through school platforms. The study showed parental satisfaction with the online health education awareness program. They exhibited enthusiasm and desire for further similar sessions in the future. The results demonstrated an enhancement in parental awareness about common health conditions among school children. This study may be replicated on a larger scale in the schools of Pakistan.